Research of Kinematic Parameter Calibration Method of 3-R2U2S Parallel Robot - Yuandong Wang; Jie Gao (Jixie chuandong)
Abstract The general methods of parameter calibration of parallel robot mechanism are analyzed， and a new parameter calibration method based on automatic cooperation principle for 3-R2U2S parallel robot is proposed. The principle is that all the influencing factors of positioning error are attributed to the change of robot mechanism parameters， and the comprehensive correction rod length influence factor including various error sources is obtained， then the more accurate kinematics inverse equation is finally obtained. In order to check the reliability of the method， the calibration experiment center of 3-R2U2S parallel robot prototype is built. In the workspace， 50 points are randomly selected for testing， and their coordinates are replaced into the modified inverse kinematic solution equation， and the theoretical input value of the driving angle of each branch chain is obtained. The test result shows that the deviation between the theoretical input value and the actual input value is controlled within the allowable range， which verifies the accuracy and reliability of using the automatic cooperation method to solve the modified rod length to establish the kinematic inverse solution equation of 3-R2U2S parallel robot.